A prospective study of the prevalence of tuberculosis and bacteraemia in Bangladeshi children with severe malnutrition and pneumonia including an evaluation of Xpert MTB/RIF assay. - Mohammod Jobayer Chisti; Stephen M Graham; Trevor Duke; Tahmeed Ahmed; Hasan Ashraf; Abu Syed Golam Faruque; Sophie La Vincente; Sayera Banu; Rubhana Raqib; Mohammed Abdus Salam (PLoS ONE)
Background Severe malnutrition is a risk factor for pneumonia due to a wide range of pathogens but aetiological data are limited and the role of Mycobacterium tuberculosis is uncertain. Methods We prospectively investigated severely malnourished young children (<5 years) with radiological pneumonia admitted over a 15-month period. Investigations included blood culture, sputa for microscopy and mycobacterial culture. Xpert MTB/RIF assay was introduced during the study. Study children were followed for 12 weeks following their discharge from the hospital. Results 405 eligible children were enrolled, with a median age of 10 months. Bacterial pathogens were isolated from blood culture in 18 (4.4%) children, of which 72% were Gram negatives. Tuberculosis was confirmed microbiologically in 7% (27/396) of children that provided sputum - 10 by culture, 21 by Xpert MTB/RIF assay, and 4 by both tests. The diagnostic yield from induced sputum was 6% compared to 3.5% from gastric aspirate. Sixty (16%) additional children had tuberculosis diagnosed clinically that was not microbiologically confirmed. Most confirmed tuberculosis cases did not have a positive contact history or positive tuberculin test. The sensitivity and specificity of Xpert MTB/RIF assay compared to culture was 67% (95% CI: 24-94) and 92% (95% CI: 87-95) respectively. Overall case-fatality rate was 17% and half of the deaths occurred in home following discharge from the hospital. Conclusion and significance TB was common in severely malnourished Bangladeshi children with pneumonia. X-pert MTB/RIF assay provided higher case detection rate compared to sputum microscopy and culture. The high mortality among the study children underscores the need for further research aimed at improved case detection and management for better outcomes.